BONE STRESS INJURIES IN RUNNERS - A HOLISTIC APPROACH - Alicja Toczyłowska,; Mateusz Muras,; Władysław Hryniuk,; Julia Kwiecińska,; Jacek Sitkiewicz,; Łukasz Bialic,; Lidia Mądrzak,; Marta Korchowiec,; Wiktor Chrzanowski,; Katarzyna Krzyżanowska, (International Journal of Innovative Technologies in Social Science, 2025)
Objective: Bone stress injuries (BSIs), ranging from periosteal edema to stress fractures, are highly prevalent in runners due to repetitive loading exceeding bone adaptation capacity. Delayed diagnosis prolongs recovery. This review synthesizes current knowledge on BSI pathophysiology, risk factors, diagnosis, management, and prevention in runners, highlighting the complexity of the problem.Methods: A literature review was conducted using publicly available sources accessed via PubMed and Scopus.Key Findings: BSIs arise from an imbalance between microdamage accumulation and repair, influenced by biological and biomechanical factors. Magnetic resonance imaging (MRI) is the diagnostic gold standard, recommended after initial plain radiography. Management prioritizes conservative measures; surgery is reserved for high-risk fractures (e.g., prone to nonunion) or conservative failure. Prevention strategies include individualized training programs, nutritional optimization, and preparticipation screening.Conclusions: Early diagnosis and a multidisciplinary approach—focusing on risk factor identification, timely intervention, treatment, and prevention—are crucial for reducing BSI incidence and accelerating recovery in runners. Further research is needed to validate novel treatments and standardize risk factor detection systems for injury prevention.